Bereaved parents’ perceptions of their cancer-ill child’s last month with or without palliative care - a nationwide study - Stenmarker, Margaretha; Pohlkamp, Lilian; Sveen, Josefin; Kreicbergs, Ulrika (Frontiers in Oncology, 2024)
BackgroundCancer is still the leading cause of non-accidental death in childhood, although the majority of children diagnosed in high-income countries survive their illness. In accordance with international standards, equal and early access to palliative care should be available to children and adults. Yet communication and prognostic disclosure may influence the timing of involvement in palliative care. Purpose: To investigate whether parents perceived that their child received palliative care and to what extent that contrasted parents’ perceptions of their child’s care and symptoms in the last month of life.MethodsA nationwide population-based parental questionnaire study in Sweden, one to five years after their child’s death (n=226). Descriptive statistics were used.ResultsA majority of parents (70%) reported that they were aware that their child received palliative care and they were informed about the incurable disease (57%) within 3 months before the child died. The most common diagnosis among children receiving palliative care was a brain tumor (45%) with a disease related death (90%) and the care was often received at home (44%). Based on the reports of parents who felt that their child did not receive palliative care, 45% were informed within days or hours about the child’s incurable disease, 45% of these children were diagnosed with leukemia, 60% died at the intensive care unit, and 49% died of treatment-related complications. It was most common for families who lived in urban areas (28%) to report their child received palliative care, in comparison to families living in sparsely populated areas (11%). A significant proportion of parents whose child received palliative care (96%) stated that the healthcare professionals were competent in caring for their child, for those who reported no palliative care it was slightly lower (74%). In both groups many children were affected by multiple symptoms the last month of life.ConclusionsThe study findings highlight the role of understanding parental perceptions of pediatric palliative oncology care, the role of initiating palliative care early, the need of access to national equitable PC and professional competence across the lifespan, regardless of diagnosis and place of residence.